Efficacy and safety of the traditional Chinese formula Shengjiang powder combined with conventional therapy in the treatment of diabetic kidney disease: a systematic review and meta-analysis - Zhang, Zhuofan; Liu, Yingna; Qian, Jiawen; Jiang, Wenli; Cao, Liqun; Li, Zhiyu; Chen, Hongbo; Liu, Shan (Frontiers in Endocrinology, 2024)
Objective: To investigate the efficacy and safety of Shengjiang powder as a treatment for DKD. Methods: A comprehensive search was performed in eight databases from their inception to December 30, 2023, to identify relevant RCTs. The inclusion criteria were diagnosis of DKD and intervention including TCM that contained Shengjiang powder. Two researchers independently conducted literature screening and data extraction, utilizing the Rob2 tool and GRADE to assess the quality of the RCTs. Meta-analysis was carried out using RevMan 5.4.1 and Stata 15.0. Results: As a result of the search, 23 RCTs comprising 1,682 patients. The interventions resulted in significant reductions in all the assessed indicators: 24-h urinary protein, UAER, mALB, BUN, Scr, FBG, 2hPG, HbA1c, total cholesterol, and Triglycerides. Together the results showed that Shengjiang powder, in conjunction with conventional therapy, is an effective treatment of DKD.Subgroup analyses, considering duration, stage, blood glucose control levels, baseline blood glucose levels, and baseline Scr levels indicated that shorter duration treatment had a greater effect on UAER, 2hPG, and HbA1c. Additionally, Shengjiang powder was more effective in reducing 24-h urinary protein, Scr, and 2hPG in stage IV patients compared to corresponding values at other stages.However, with respect to FBG, the treatment was more effective in stage II/III. Shengjiang powder also, reduced Scr levels significantly in patients with higher baseline Scr and reduced urinary protein excretion with stricter blood glucose control. The interventions had additional lipid-regulating effects 4 删除[author]: